การพัฒนาโปรแกรมการเรียนการสอนคณิตศาสตร์สำหรับเด็กวัยอนุบาล โดยใช้ศูนย์การเรียนที่มีสัญญาการเรียน - คัทนีย์ แก้วมณี (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The purpose of this research were to develop the Mathemat’cs Instructional Program by using learning centers with learning contract for preschoolers and to study the program implementation process. The subjects were sixty first preschool year students of the second semester at Wat Parinayok Preschool in the academic year of 2000. The preschoolers were randomly assigned to the experimental group and the control group, thirty eacii. Program development stages were consisted of 4 phases; phase 1, studying preliminary information; phase 2, constructing the program; phase 3, field testing; and phase 4, revising the program. The duration of field testing was scheduled for 14 weeks; 2 weeks of pre-test, 10 weeks of experiment, and 2 weeks of post-test. The pre-test and post-test were measured by mathematical ability test. The research results were as follows: 1) After the field testing, the mathematical ability scores of the experimental group were significantly higher than those of the control group at the .01 level. 2) The program implementation process consisted of arrangement of environment, classroom management and instruction. 3) The revised Mathematics Instructional Program by using learning centers with learning contract for preschoolers contained a weekly unit of an integrated thematic instructional approach using the steps of learning center activities with learning contract. The program content consisted of its underlying theoretical approach, principles, roles and responsibilities of the program user and the target students, program structure and features, and program materials which were 1) a teacher’s handbook for program implementation, 2) sets of the planned activities, and 3) tools of instructional evaluation.